ChemInform Abstract: 3‐Methyl‐1‐sulfoimidazolium Ionic Liquids as Recyclable Medium for Efficient Synthesis of Quinoline Derivatives by Friedlaender Annulation. Issue 23 (June 2015) - Sarma, Parishmita; Dutta, Arup Kumar; Gogoi, Pinky; Sarma, Bipul; Borah, Ruli
Abstract Various quinoline derivatives are obtained under solvent‐free reaction conditions using the title ionic liquids as reaction medium.